Chemotherapy-Induced Peripheral Neuropathy: Pathophysiology, Diagnosis, and Treatment - Justitia, Ica; Dewi, Putri Krishna Kumara; Fauzi, Yanuar Rahmat; Hunaifi, Ilsa (Universitas Airlangga, 2024)
Highlight: Chemotherapy induces neurotoxicity through DNA crosslink, impaired calcium homeostasis, mitochondrial damage, increased reactive oxygen species, pro-inflammatory cascade, axon degeneration, and programmed cell death. CIPN has a primary impact on the sensory neuron. CIPN is diagnosed based on the patient's history, chemotherapy history, and neurologic examination. Some pharmacological and non-pharmacological treatments are hypothesized to reduce CIPN symptoms, but only duloxetine is recommended. ABSTRACT Chemotherapy-induced peripheral neuropathy (CIPN) is the most common and severe neurological side effect of many commonly used chemotherapy agents. It affects more than 60% of cancer patients. Approximately 30%–40% of patients have persistent symptoms five months or longer after stopping treatment. Even years after completing chemotherapy, some patients still experience CIPN symptoms. CIPN increases the annual cost of healthcare, leads to detrimental dose reduction and even cessation of treatment, and severely affects cancer survivors’ quality of life. Chemotherapy induces neurotoxicity through a variety of mechanisms that lead to neuronal cell damage or cell death. This mechanism of neurotoxicity varies depending on the specific agent. CIPN is characterized predominantly by sensory axonal peripheral neuropathy. Motor and autonomic symptoms may appear, but less frequently. To diagnose CIPN, a thorough patient's history and neurological examination are required. The current approach to CIPN management focuses on managing the symptoms of neuropathic pain and reducing or stopping the chemotherapy agent when CIPN manifests. There is no proven or advised prophylaxis therapy for CIPN. The point of this review was to talk about how some commonly used chemotherapy agents (such as platinum-based compounds, taxanes, vinca alkaloids, bortezomib, and thalidomide) cause CIPN, how to diagnose it, and the newest treatments that are available.